2020
DOI: 10.1037/ser0000325
|View full text |Cite
|
Sign up to set email alerts
|

Pragmatic trial of brief warrior renew group therapy for military sexual trauma in VA primary care.

Abstract: This is a pragmatic trial of a brief version of Warrior Renew, an emerging evidence-based treatment for military sexual trauma (MST) delivered in a Department of Veterans Affairs women’s health clinic primary care setting. The full protocol meets twice a week for 12 weeks (24 sessions); however, Brief Warrior Renew meets for 8 sessions. Brief Warrior Renew is a manualized protocol addressing coping skills for affect management (e.g., triggers and anxiety) and unique aspects of MST including anger–resentments d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 50 publications
0
9
1
Order By: Relevance
“…Similar findings were found with nonveteran women in a residential substance abuse treatment program (Hemma, McNab, & Katz, 2018). Free-text comments written by participants stated addressing holograms was pivotal in their recovery (Hemma et al, 2018;Katz & Sawyer, 2019). One client summed her therapy experience as, "profound liberation and divestment of a hologram that no longer serves" (Katz & Sawyer, 2019).…”
Section: Effectiveness Of Holographic Reprocessing Therapymentioning
confidence: 57%
See 2 more Smart Citations
“…Similar findings were found with nonveteran women in a residential substance abuse treatment program (Hemma, McNab, & Katz, 2018). Free-text comments written by participants stated addressing holograms was pivotal in their recovery (Hemma et al, 2018;Katz & Sawyer, 2019). One client summed her therapy experience as, "profound liberation and divestment of a hologram that no longer serves" (Katz & Sawyer, 2019).…”
Section: Effectiveness Of Holographic Reprocessing Therapymentioning
confidence: 57%
“…Five outcome studies of Warrior Renew, demonstrated decreased negative symptoms such as anxiety, depression, PTSD, and negative cognitions and increased positive factors such as optimism, satisfaction with life, and perceived attachment with large effect sizes and low dropout rates for female veterans (Katz, 2016;Katz, Park, Cojucar, Huffman, & Douglas, 2016;Katz & Sawyer, 2019), including a long-term study that found improvement were sustained 12 months from baseline (Katz et al, 2015). Similar findings were found with nonveteran women in a residential substance abuse treatment program (Hemma, McNab, & Katz, 2018).…”
Section: Effectiveness Of Holographic Reprocessing Therapymentioning
confidence: 64%
See 1 more Smart Citation
“…It is not clear if perhaps, contextual factors such as living in an unsafe, potentially dangerous, or unpredictable world due to the 6 KATZ COVID-19 pandemic influenced a general sense of anxiety distinct from reducing anxiety-related symptoms assessed on the GAD-7 or related to skills in how to handle a trigger. Compared to in-person brief warrior renew conducted with women veterans (Katz & Sawyer, 2020), this evaluation had a lower effect size on the PHQ-9 (1.19 vs. .77) but a similar effect size on the GAD-7 (.85 vs. .84). The in-person evaluation used the full version of the PTCI demonstrating very large effect sizes (total scale: 1.42) compared to the brief version in this evaluation with a moderate effect size (total scale: .63) with similar results on subscales.…”
Section: Discussionmentioning
confidence: 73%
“…This program evaluation examined an eight-session brief version of warrior renew (Katz & Sawyer, 2020) to address symptoms related to military sexual trauma but modified for video teleconferencing. This is the first program evaluation of warrior renew (Katz, 2014) delivered in this novel video format.…”
Section: Telehealth Carementioning
confidence: 99%